093. A Rare Case of Giant Urethral Stone Removal by Uretrolithotomy in A Patient with Urethral Diverticles - Umam, Akmal Fawzi; Habiby, Redha Ramadhana; Sutapa, Hendra; Yulizar, Deddy Rasyidan; Rahman, Eka Yudha (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : A rare case involving a 54-year-old male who complained of persistent micturition pain for 10 years. The patient experienced urinary incontinence and reported a palpable mass under his testicle. Methods : Clinically, a mass was found in the perineum, and imaging studies using bipolar voiding urethrocystography showed a urethral stricture with urethral stones measuring 4 cm in diameter. Results : The patient underwent urethrolithotomy surgery for urolithiasis. After surgery, the patient was admitted to the general ward for 3 days and then discharged. Panendoscopic and urethrography evaluations revealed no residual stones, and urethral dilation was noted. Conclusion : Urethral stones are rare and may result from calculus migration from the upper urinary tract or structural abnormalities of the urethra. The occurrence of stones within the diverticulum is reported to range from 1% to 10% and often presents with nonspecific symptoms. It is important to evaluate the size and location of the urethral calculus, as well as the underlying urethral pathology.